Reduced doses of herbicides to control weeds in barley crops under temperate conditions - Barros, José (2011)
Yield losses in cereal crops under temperate climate conditions due to weed-crop competition, namely Lolium rigidum G., can reach up to 80%, depending on the season and infestation level. Nevertheless, the costs of chemical weed control and the environmental impact caused by herbicides recommend the search for strategies to reduce their input. Therefore, the aim of this work was to study the possibility of reducing the input of different post-emergence herbicides (diclofop-methyl + fenoxaprop–p-ethyl and amidosulfuron + iodosulfuron-methyl-sodium) to control Lolium rigidum G. and broad-leaf weeds in barley under no-till, and to monitor the effect on weed population levels and crop yields. A field experiment was carried out in 2007-2008 and 2008-2009, in an experimental farm in the south of Portugal, combining different herbicide doses applied at different weed development stages. Results show that, for all herbicide doses, the earlier application provides higher weed control efficacy and higher grain yields, indicating that the reduction of doses is possible while maintaining satisfactory crop grain yields.